Axial interactions in the mixed-valent Cu(A) active site and role of the axial methionine in electron transfer - Tsai, Ming-Li (National Academy of Sciences, 2013)
Within Cu-containing electron transfer active sites, the role of the axial ligand in type 1 sites is well defined, yet its role in the binuclear mixed-valent Cu(A) sites is less clear. Recently, the mutation of the axial Met to Leu in a Cu(A) site engineered into azurin (Cu(A) Az) was found to have a limited effect on E(0) relative to this mutation in blue copper (BC). Detailed low-temperature absorption and magnetic circular dichroism, resonance Raman, and electron paramagnetic resonance studies on Cu(A) Az (WT) and its M123X (X = Q, L, H) axial ligand variants indicated stronger axial ligation in M123L/H. Spectroscopically validated density functional theory calculations show that the smaller ΔE(0) is attributed to H(2)O coordination to the Cu center in the M123L mutant in Cu(A) but not in the equivalent BC variant. The comparable stabilization energy of the oxidized over the reduced state in Cu(A) and BC (Cu(A) ∼ 180 mV; BC ∼ 250 mV) indicates that the S(Met) influences E(0) similarly in both. Electron delocalization over two Cu centers in Cu(A) was found to minimize the Jahn–Teller distortion induced by the axial Met ligand and lower the inner-sphere reorganization energy. The Cu–S(Met) bond in oxidized Cu(A) is weak (5.2 kcal/mol) but energetically similar to that of BC, which demonstrates that the protein matrix also serves an entatic role in keeping the Met bound to the active site to tune down E(0) while maintaining a low reorganization energy required for rapid electron transfer under physiological conditions.